Sugarcane biomass conversion influenced by lignin - Schmatz, Alison A. [UNESP]; Tyhoda, Luvuyo; Brienzo, Michel [UNESP] (Wiley, 2020)
Plant biomass residues are renewable sources for the production of biofuels and high-value macromolecules. Sugarcane bagasse is one such plant biomass residue that is available from the sugar-processing industry. It is used as a raw material for biobased ethanol production. However, some of its properties and its behavior during processing have a major inhibitory effect on its successful conversion. Chief among these inhibitory properties are the lignin content, its distribution in plant tissues, and its chemical properties. These make the materials naturally resistant to bioconversion processes. Further, lignin and carbohydrate degradation products can be formed during acid pretreatment, which is one of the major steps during biomass conversion to bioethanol. These products negatively affect the liberation of fermentable sugars and the yield of ethanol during the fermentation stage of the conversion process. Other factors that also have an influence on the production of fermentable sugar are related to the different structural arrangement of plant tissues (cane fractions of the node, internode, and external fraction), as well as biomass variety. Biomass varieties with low lignin content result in an improved yield of fermentable sugars, which in turn contributes to improved viability of the second-generation bioethanol production processes. By selecting sugarcane varieties with the best properties, ethanol production can be increased without increasing the total area under cultivation. Efforts have been dedicated to reducing biomass recalcitrance by classical and precision breeding. Genetic modification of sugarcane alters the genes responsible for the encoding enzymes for lignin biosynthesis, generating sugarcane with low recalcitrance. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.
Keywords: classical breeding; precision breeding; pretreatment; pseudo-lignin; recalcitrance; second-generation ethanol